Oligonucleotides‐decorated‐poly(N‐vinyl pyrrolidone) nanogels for gene delivery. Issue 2 (2nd August 2013) - Dispenza, Clelia; Adamo, Giorgia; Sabatino, Maria Antonietta; Grimaldi, Natascia; Bulone, Donatella; Bondì, Maria Luisa; Rigogliuso, Salvatrice; Ghersi, Giulio
ABSTRACT Pulsed electron‐beam irradiation of a semi‐dilute poly(N‐vinyl pyrrolidone) (PVP) aqueous solution in the presence of acrylic acid has led to a carboxyl functionalized nanogel system. Nanoparticles hydrodynamic size and surface charge density, in water and as a function of pH, were investigated by dynamic light scattering and laser doppler velocimetry, respectively. Nanogels (NGs) were proved not to be cytotoxic at the cellular level. Indeed, they rapidly bypass the cellular membrane to accumulate in specific cell portions of the cytoplasm, in the perinuclear area. The availability of pendant carboxyl groups on the crosslinked PVP NGs core prompted us to attempt their decoration with a single strand oligonucleotide, which holds a terminal amino group. The recognition ability of the attached single helix of its complementary strand was investigated. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39774.